Contactless determination of nuclear compressibility using 3D image- and model-based analysis of drug-induced cellular deformation - Gladilin, Evgeny; Schulz, Martin; Kappel, C.; Eils, Roland (Journal of microscopy, 2010)
Mechanical properties of the chromatin-bearing nucleus in normal and pathological cells are of general interest for epigenetics and medicine. Conventional techniques for quantitative measurements of material properties of cellular matter are based on application of controlled forces onto the cellular or nuclear boundary and do not allow probing intracellular structures that are not directly accessible for physical contact inside the living cell. In this work, we present a novel approach for contactless determination of the nuclear compressibility (i.e. the Poisson's ratio ν) in living cells by means of image- and model-based analysis of drug-induced cell deformation. The Poisson's ratio of the HeLa cell nucleus is determined from time-series of 3D images as a parameter of constitutive model that minimizes the dissimilarity between the numerically predicted and experimentally observed images.